Employer Branding Dimension through Social Network Analysisv - Aryasree Anil, Murale Venugopalan, Anand Krishnan R (International Journal of Advanced Science and Technology, 2020)
Employer Branding is an evolving concept where an employer – any kind of organisation, is promoted as an employer of choice. The benefits that employees reap by being a part of an organisation forms employer branding. We contend that when representatives use Information Technology to share and access business-related encountersforthrightly across the organisations or various firms, their desires and appraisals of work environments change. We have gathered 1000 reviews about 10 of the worthiest and 10 of the least worthy businesses according to Great Place to Work from Glassdoor (an online publicly supported manager marking stage). Utilizing the text2data API to dissect the information, we used algorithm to synthesis key words that have an impact on the employer brand. we recognize propositions, marking offers that current, previous, and potential representatives care about when they by and large assess managers. These kry themed evolved out of our analysis includes (1) social components of work, (2) Compensation and other benefits, (3) the degree to which abilities can be applied in significant manners, (4) Supportive Management, (5) Career Development & Learning Opportunities, (6) Autonomy & feedback (7) work/life balance. We explain that these worth suggestions don’t make a difference to a similar degree and show how their relative valences and loads contrast across associations, particularly if organizations are viewed as especially positive or negative work environments. From these findings, we show how managers can utilize publicly supported boss marking insight to get incredible work environments that draw in profoundly qualified representatives.